Interrelationship Performance Indicators Model of Sustainable Procurement in Higher Education - Rangga Primadasa; Dina Tauhida (Universitas Ahmad Dahlan Indonesia, 2021)
Sustainable procurement is developing among practitioners and academics, but not many have done this research with the object of higher education institutions. This study succeeded in obtaining twelve indicators of sustainable procurement in higher education in Indonesia. The interpretive structural modeling method is used to model these indicators so that a four-level model is obtained, where the first level consists of seven indicators, the second level is one indicator, the third level is two indicators, and the fourth level is two indicators. In addition, the twelve indicators were also grouped using MICMAC analysis into four quadrants. Eight indicators are included in the autonomous indicators quadrant, four indicators are included in the independent indicators quadrant. Nothing is included in the dependent indicators and linkage indicators quadrant. This study proposes to the management of higher education to improve the performance of sustainable procurement, starting from level four indicators, namely the existence of routine monitoring and sustainability criteria (P12) and there is awareness of sustainable procurement on campus internals (P2).